Spokane Paper - The Assay and Valuation of Gold-Bullion - Frederic P. Dewey (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1910)
The Bureau of the Mint of the United States Treasury maintains 13 ofEces for the purchase of gold-bullion, and this paper describes an investigation to establish the reasonable differences in the assay-results at the various institutions which may be commercially allowable in the settlements between them. Beginning with the comparative assay of proof-gold at the Philadelphia mint and the Utrecht mint, which shows 0.00002 as the closest agreement now possible, nine tables of comparative results, taken from the regular work of the service, are given..These tables begin with very fine gold, produced in an electrolytic refinery, showing close agreement in the assay-results, and follow through decreasing gold fineness and increasing amounts and complexity of base metals to very impure and complex bars produced at cyanide-mills, some of which give widely-varying results. Next is given a series of results on samples, prepared and sent out to various laboratories in the service, to test the influence of different metals and various combinations upon the agreement of the assay-results ; 11 samples were sent out and each one was assayed from 44 to 71 times, making a total of 623 assays. To these ire added 107 assays of identical samples of coin-gold. On a previous occasion,' I have endeavored to show the degree of accuracy that may be expected in the ordinary everyday analysis of various materials, and on another occasion,2